Correlation between skin, bone, and cerebrospinal fluid layer thickness and optical coefficients measured by multidistance frequency-domain near-infrared spectroscopy in term and preterm infants - Demel, Anja; Feilke, Katharina; Wolf, Martin; Poets, Christian F; Franz, Axel R (Journal of biomedical optics, 2014)
Near-infrared spectroscopy (NIRS) is increasingly used in neonatal intensive care. We investigated the impact of skin, bone, and cerebrospinal fluid (CSF) layer thickness in term and preterm infants on absorption-(μa) and/or reduced scattering coefficients (μs′) measured by multidistance frequency-domain (FD)-NIRS. Transcranial ultrasound was performed to measure the layer thicknesses. Correlations were only statistically significant for μa at 692 nm with bone thickness and μs′ at 834 nm with skin thickness. There is no evidence that skin, bone, or CSF thickness have an important effect on μa and μs′. Layer thicknesses of skin, bone, and CSF in the range studied do not seem to affect cerebral oxygenation measurements by multidistance FD-NIRS significantly.